(untitled) (KULT_online, 2025)
Jean-Pierre Dupuy takes on the challenge of making doomsaying possible again. He begins with examinations of current approaches to understanding catastrophe. Building on the works of Henri Bergson and Ivan Ilich (among other figures), Dupuy offers a thought-provoking reconceptualization of catastrophe through a reconsideration of its temporal qualities and a correction of counterproductive tendencies in current systems of economic, social, and political arrangement. Concise and astute, Dupuy’s book has much to contribute to ongoing discussions of catastrophe.